DETECTION OF MICROPLASTICS IN BLOOD CLAM (Tegillarca granosa) AND GREEN MUSSEL (Perna viridis) FROM BERINGHARJO MARKET, YOGYAKARTA CITY - Nurul Suwartiningsih; Shabrina Lailani; Adhita Sri Prabakusuma; Dian Eka Wijayanti (LPPM Universitas PGRI Semarang, 2024)
Plastic is one of the main pollutants in the ocean due to its persistent nature. Plastic in waters can be broken down into pieces <5 mm in size, called microplastics, and enter the bodies of aquatic biota such as shellfish. The objectives of this research was to analyze the abundance and identify the characteristics of microplastics in blood clam and green mussel from Pasar Beringharjo, Yogyakarta City. The method in this research is to sample shellfish from Pasar Beringharjo. The shellfish samples obtained had their meat removed and soaked in 10% KOH for 3 days. The isolation results were filtered and the microplastics obtained were observed under a light microscope to determine their abundance and characteristics. The polymers that make up microplastics are analyzed by FTIR. The abundance and characteristics of microplastics between shellfish kinds were compared using the Mann Whitney test. The results showed that the abundance of microplastics in blood clam (average 839.25 ± 144.24 microplastics/individual) was higher compared to green mussel (average 703.75 ± 159.21 microplastics/individual), but not significantly different (p>0.05). The form of microplastic that dominates in both kinds of shellfish is fragments. The most common color of microplastics found in both kinds of shellfish was black and brown. The size of microplastics in both kinds of shellfish is dominated by the range 0-100 µm. FTIR results indicate the type of nylon polymer (polyamide). Microplastics in blood clam and green mussel from Pasar Beringharjo, Yogyakarta City have almost the same abundance and characteristics.